2017
DOI: 10.14740/jocmr2829w
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Thrombolytic Therapy in Acute Submassive Pulmonary Embolism: Follow-Up Study

Abstract: BackgroundThrombolysis in acute submassive pulmonary embolism (PE) remains controversial. So we studied impact of thrombolytic therapy in acute submassive PE in terms of mortality, hemodynamic status, improvement in right ventricular function, and safety in terms of major and minor bleeding.MethodA single-center, prospective, randomized study of 86 patients was conducted at LPS Institute of Cardiology, G.S.V.M. Medical College, Kanpur, India. Patients received thrombolysis (single bolus of tenecteplase) with u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 15 publications
1
20
0
Order By: Relevance
“… 3 Submassive PE is associated with high mortality and adverse short-term outcomes, and therefore effective and safe treatment must be provided promptly. 4 The management of patients with submassive PE depends on the clinical presentation and risk classification. By the 2014 European Society of Cardiology (ESC) criteria, our patient had intermediate to high risk of PE.…”
Section: Discussionmentioning
confidence: 99%
“… 3 Submassive PE is associated with high mortality and adverse short-term outcomes, and therefore effective and safe treatment must be provided promptly. 4 The management of patients with submassive PE depends on the clinical presentation and risk classification. By the 2014 European Society of Cardiology (ESC) criteria, our patient had intermediate to high risk of PE.…”
Section: Discussionmentioning
confidence: 99%
“…The treatment group then received a weight-adjusted bolus dose of tenecteplase. The control group received the same volume of placebo (normal saline), followed by a maintenance dose of heparin [ 11 ].…”
Section: Reviewmentioning
confidence: 99%
“…There was also a significant difference between mean hospital stay in the tenecteplase group at 8.1 days versus the placebo group at 11.1 days (p = 0.001). Lastly, there was a statistically significant improvement in right ventricular function between both groups (p = .001) with 70% from the tenecteplase arm experiencing improvement in right ventricular function while 40% experienced an improvement in the placebo arm (p = 0.001) [ 11 ].…”
Section: Reviewmentioning
confidence: 99%
“…However, in the results section they have written that 52% (n = 16) of the subjects presented with shock at admission or within 48 h following admission. It is not clear how many patients presented with massive PE; 8 or 16?The authors concluded that thrombolytic therapy can be considered for patients with both massive and submassive PE, However, the value of thrombolysis in acute submassive PE remains controversial in the current studies 2, 3. In a recent article, Desai and colleagues evaluated 3253 PE patients with hemodynamically stable right-sided heart failure 2 .…”
mentioning
confidence: 99%
“…There was no significant difference in mortality between hemodynamically stable PE patients with right ventricular dysfunction who received thrombolytic agents compared with those who did not 2 . In another single-center, prospective, randomized study of 86 patients with submassive PE, patients were divided into two groups: group I patients received thrombolysis (single bolus of tenecteplase) with unfractionated heparin and group II patients received placebo with unfractionated heparin 3 . In this study, Sinha et al found that patients with acute submassive PE do not derive overall mortality benefit, recurrent PE and rehospitalization with thrombolytic therapy 3 .…”
mentioning
confidence: 99%